Investigation of Mutations in Cleavage and Fusion regions within Spike gene of SARS-CoV-2 - Saber, Noor; Kandala, Nuha J (Iraqi Journal of Science, 2025)
The Furin cleavage site and fusion peptide are critical regions in the Spike protein of SARS-CoV-2. The activation of the spike protein relies on furin cleavage, whereas the fusion peptide is critical for merging the viral envelope with host cell membranes. This study aims to map the mutations in the S1/S2 Furin, S2’ cleavages sites, and fusion peptide regions within Iraqi isolates, examining the variability and conservation of these critical sites. Our study includes 14 SARS-CoV-2 Sanger sequenced fragments coupled with data mining of the 1043 genomic dataset of Furin/ S2’ cleavage sites and fusion peptide regions extracted from whole genome sequences, representing the entire entry of Iraq to GISAID during the pandemic. The current analysis identifies a mutational hotspot located within the Furin cleavage region at codon P681. The proline at this position changed to arginine in the Delta variant and subsequent sublineages. However, this change was displaced by P681H in Omicron variants and related newly emerging strains. Furthermore, the combination of P681H and N679K mutations enhances the basic nature of the site, making it a more favourable target for Furin, thereby boosting the Spike protein activation process. The investigation emphasizes the prevalence of D614G, H655Y, and D796Y mutations as substantial factors influencing viral transmissibility and pathogenicity. These mutations persist in global strains, indicating their role in the virus’s evolutionary trajectory. The conservative nature of the Furin and S2’ cleavage sites underscores its critical role in viral transmissibility and pathogenicity and adaptability in various proteases environment in the host cell. Mutations such as A688S, S698L, A701V, and S704L, which can impact vaccine-induced antibody sensitivity, were also detected, highlighting the ongoing challenge of maintaining vaccine efficacy against evolving strains.